Les maîtres de l’eau - Guy Lemeunier (Mélanges de la Casa de Velázquez, 2006)
The erstwhile kingdom of Murcia lies at the centre of Spain’s arid zone. Agrarian activities there are largely dependent on irrigation, the infrastructure for which was developed following the recovery of the 16th century. Rather than the physical ways in which the sharing of water resources worked, this article examines the legal, political and social framework of water sharing and the way it evolved. Outside the principal river valleys, ownership of water was generally separate from ownership of land, albeit there were intermediate formulae also. However, the evidence shows that in the course of the modern age the tendency towards concentration was even more marked in the case of water rights than in the case of land ownership. Local political authorities saw their decision-making powers circumscribed in the face of irrigators’ associations and the lobbies of the water « masters ». Fragmentation of resource management hindered the transition to large-scale water management essential to agricultural progress.